Return of the 1950s housewife? How to stop coronavirus lockdown reinforcing sexist gender roles - Chung, Heejung (2020)
Alors que le virus COVID-19 se propage à travers le monde, de nombreux gouvernements ont fermé les écoles , les crèches et autres établissements de garde d'enfants. Avec de plus en plus de personnes travaillant à domicile , il est probable que de nombreuses familles se retrouveront dans une situation où les deux parents essaient de travailler depuis la table de la cuisine tout en essayant de faire l'école à la maison aux enfants . En plus des tâches ménagères habituelles, comme la cuisine et le ménage, ces tâches peuvent représenter une charge supplémentaire pour de nombreux parents à l'heure actuelle. Il est cependant probable que même si les deux parents sont désormais à la maison, une grande partie des tâches « domestiques » reposera toujours sur les épaules des femmes de la maison. Tout comme la ménagère des années 1950, les femmes devront non seulement préparer des repas savoureux, garder la maison propre et bien rangée et divertir les enfants, mais elles devront également faire tout cela tout en travaillant à domicile.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; charge mentale; conciliation famille-travail; covid-19; discipline; famille; pandémie; projet charge mentale; périodes historiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

The COVID-19 pandemic has increased the care burden of women and families - Power, Kate (Sustainability: Science, Practice and Policy, 2020)
While women were already doing most of the world’s unpaid care work prior to the onset of the COVID-19 pandemic, emerging research suggests that the crisis and its subsequent shutdown response have resulted in a dramatic increase in this burden. It is likely that the negative impacts for women and families will last for years without proactive interventions. What we commonly refer to as “the economy” would not function without the (often unrecognized) foundation of work provided by the “care economy”: the reproduction of everyday life through cooking, raising children, and so forth. The paid economy has slowed not only because people are physically not allowed into workplaces, but also because many families currently need to raise and educate their children without institutional support, which is reducing remunerated working hours and increasing stress. It has long been recognized that gross domestic product ignores the care economy and heterodox economists have promoted alternative economic systems that could value care work and facilitate a fairer sharing of domestic labor while promoting environmental and economic sustainability. This policy brief builds on recent work on the care economy to explore implications of the COVID-19 pandemic and opportunities for addressing the burden of unpaid care work.
https://cieg.unam.mx/covid-genero/pdf/reflexiones/academia/the-care-burden.pdf
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; care; covid-19; famille; genre; périodes historiques; ressource en ligne; thématiques; travail